Firm Size as Moderator Effect of Profitability and Solvency on Audit Completion Period - Dewi, Ni Putu Anggistya; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2017)
The audit completion period is measured from the closing date of the financial year to the date the audit report is completed by the independent auditor. The length of time the completion of the audit will affect the timeliness in the delivery of audited financial statements. Timely or not, the delivery of audited financial statements is much influenced by the condition of the company in this study seen from the profitability and solvency of the company, where if there is good news, then the company will ask the auditor as soon as completed audit so that audited financial statements can be published on time. Conversely, if  there is bad news, then companies tend to be late publishing audited financial statements.This study aims to empirically test the size of the company as a moderator of the effect of profitability and solvency on the audit  completion period.  This research was conducted at a manufacturing company listed on Indonesia Stock Exchange 2012-2015. The number of samples taken by 67 manufacturing companies, using purposive sampling method. The type of data used is secondary data in the form of financial statements of manufacturing companies. Data analysis technique used is Moderated Regression Analysis.  Based on the analysis result concluded that profitability has negative and significant effect on audit completion period, solvency have positive and significant influence on audit completion period, firm size weaken the correlation between profitability at audit completion period and firm size strengthen the relation between solvability at audit completion period. Keywords: profitability, solvability, firm size, audit completion period